China - India - US Triangle Shaping Up? - Suryanarayana, Pisupati Sadasiva (2018)
China, India and the United States may feel the need to rebalance their triangular engagement following the latest Russia-India missile deal and the recent Indo-American foreign-and-defence dialogue. Will these developments negate the Sino-Indian consensus reached at Wuhan in April 2018?